2008
DOI: 10.2137/1239099041838076
|View full text |Cite
|
Sign up to set email alerts
|

ß-Glucan contents of groats of different oat cultivars in official variety, in organic cultivation, and in nitrogen fertilization trials in Finland

Abstract: ß-Glucan is a beneficial chemical compound in the diet of humans by decreasing the levels of serum cholesterol and blood glucose. The ß-glucan contents of oat groats were studied in official variety trials (1997-1999), nitrogen fertilization trials (1997-1999) and organic variety trials (1997-1998) in Finland. Eight cultivars were studied in the organic variety trials. Two of them, cultivars Puhti and Veli, were cultivated also with a conventional method at the same fields. The years 1997 and 1999 were very wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
5
15
1
1
Order By: Relevance
“…A significant effect of genotype×environment interaction on β-glucan levels in oats was also confirmed by Saastamoinen et al [31] and these authors found small differences among oat cultivars (ca. 1%) and presumed this to be genetically controlled effects too.…”
Section: Discussionsupporting
confidence: 65%
“…A significant effect of genotype×environment interaction on β-glucan levels in oats was also confirmed by Saastamoinen et al [31] and these authors found small differences among oat cultivars (ca. 1%) and presumed this to be genetically controlled effects too.…”
Section: Discussionsupporting
confidence: 65%
“…Lower water availability positively affected β-glucan in Peterson (1991); however, the opposite occurred in Doehlert et al (2001). In some studies, N fertilization incremented the β-glucan and protein contents (Fan et al, 2009;Güler, 2011); whereas in others only there was a positive effect in protein content (Saastamoinen et al, 2004;Weightman et al, 2004). In this work, only there was effect of the environment in the protein content (result not shown).…”
Section: Discussioncontrasting
confidence: 50%
“…Weightman et al (2004) evidenced that increasing ammonium nitrate rates exert a positive effect on protein content but not on b-glucan concentration of winter oats. Saastamoinen et al (2004) reported no significant effects of traditional vs. organic cultivation on b-glucan accumulation. Genetic origin and, to a minor extent, soil fertility, were found to have a large impact on oat grain components (Brennan and Cleary 2005;Peterson et al 2005).…”
Section: Introductionmentioning
confidence: 95%